Parathyroid hormone is associated with prostate cancer - Won Tae Kim; Woo Jin Bang; Sung Pil Seo; Ho Won Kang; Young Joon Byun; Xuan-Mei Piao; Pildu Jeong; Kyung-Sub Shin; Song-Yi Choi; Ok-Jun Lee; Yong-June Kim; Sang Cheol Lee; et al. (Prostate International, 2020)
Background: The present study investigated the association of serum parathyroid hormone (PTH), vitamin D, and calcium levels with prostate cancer (CaP). Methods: The study population consisted of an experimental group [459 patients including 216 patients with CaP and 243 patients with benign prostate hyperplasia (BPH)] and a prostatectomy group (47 patients who underwent radical prostatectomy). Patients with serum creatinine levels >1.4 mg/dl, parathyroid disease, and/or PTH levels <10 pg/ml were excluded. Patients with CaP and patients with BPH were compared, and the correlation between serum parameters and clinical data was determined. Preoperative and postoperative PTH levels were compared in the prostatectomy group. Results: Mean PTH levels were 41.67 ± 28.82 and 27.06 ± 17.32 pg/ml in the CaP and BPH groups, respectively (p < 0.001). When patients were divided into two groups as per prostate-specific antigen levels (≤20 or >20 ng/ml), Gleason score (≤7 or ≥8), and stage (≤T3 or ≥ T4), there was no significant difference in PTH levels between the two groups. Mean postoperative PTH levels (26.93 ± 13.58 pg/ml) were significantly lower than preoperative PTH levels (36.71 ± 21.04 pg/ml) in the same patients who underwent radical prostatectomy. Conclusion: Serum PTH levels were higher in patients with CaP than in patients with BPH and decreased significantly after radical prostatectomy. The present results suggest an association between serum PTH and CaP. Further large cohort studies are necessary to validate the present data.